Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $A$ is a $n \times n$ constant matrix. How can I prove $\det(e^A) = e^{\displaystyle \sum_{\lambda_i\in\sigma(A)} \lambda_i}$,

where $\sigma(A)$ is the multiset of eigenvalues of $A$?

The following matlab code shows this is true in $n = 3$ case:

A = rand(3)
detA = exp(sum(eig(A)))
detmA = det(expm(A))
share|cite|improve this question
prove it for diagonal matrices and use denseness of diagonalizable matrices. notice that the trace of $A$ is the sum of the eigenvalues – cats Mar 1 '13 at 20:34

You can reduce problem for diagonal matrix using the fact that every matrix can be approximated with any given precision and both functions: $e^X$ and $\det X$ are continuous. The problem with diagonal matrix is obvious.

P.S. It seems that lyj was faster than me.

share|cite|improve this answer

If you're afraid of the density of diagonalizable matrices, simply triangularize $A$. You get $$A=P^{-1}UP,$$ with $U$ upper triangular and the eigenvalues $\{\lambda_j\}$ of $A$ on the diagonal.

Then $$ \mbox{det}\;e^A=\mbox{det}(P^{-1}e^UP)=\mbox{det}\;e^U. $$

Now observe that $e^U$ is upper triangular with $\{e^{\lambda_j}\}$ on the diagonal.

So $$ \mbox{det} \;e^A=\mbox{det} \;e^U=e^{\lambda_1}\cdots e^{\lambda_n}=e^{\lambda_1+\ldots+\lambda_n}. $$

share|cite|improve this answer
Anyone trying to understand this solution: The main idea is that if the eigenvalues of $A$ are $\lambda_i$, then the eigenvalues of $e^A$ are $e^{\lambda_i}$, which you can see by using the series definition of $e^A$ and multiplying nonzero eigenvector $v_i$ as in $e^A v_i = \lambda_i v_i$. Distribute the $v_i$ through the series. Finally, the determinant of a matrix is the product of the eigenvalues, and the trace of a matrix is the sum of the eigenvalues. This explains the second to last equality in the proof above. – wkschwartz Oct 25 '15 at 23:28

You just use the Jordan normal form, $A$ is you matrix, $D$ is the Joran Form of $A$ and $S$ is the transfomration matrix, for the second equal just remember of the definition of the Matrixexponential, and that $$(SAS^{-1})^n = S A S^{-1}S A S^{-1} S A \dots S A S^{-1}=S A^n S^{-1}$$ \begin{align*} \det(\exp(A))&=\det(\exp(S D S^{-1}))\\ &=\det(S \exp(D) S^{-1})\\ &=\det(S) \det(\exp(D)) \det (S^{-1})\\ &=\det(\exp (D))\\ &=\prod_{i=1}^n e^{d_{ii}}\\ &=e^{\sum_{i=1}^n{d_{ii}}}\\ &=e^{\text{tr}D} \end{align*} As the trace is invariant this works.

share|cite|improve this answer

For an analytic method, using differential equations:

Let $f(t)= \det(e^{tA})$. Then $f'(t)=D \det(e^{tA}) \cdot Ae^{tA}=\text{tr} \left(^t \text{com}(e^{tA})Ae^{tA} \right)$. But $A$ and $e^{tA}$ commute, and $^t\text{com}(e^{tA})e^{tA}=\det(e^{tA}) \operatorname{I}_n$. Therefore, $f'(t)=\text{tr}(A)f(t)$ and $f(0)=1$, hence $f(t)=e^{\text{tr}(A)t}$. For $t=1$, $\det(e^{A})= e^{\text{tr}(A)}$.

share|cite|improve this answer
What kind of commutator is $^t\text{com}(e^{tA})$? Never seen this notation. – Faq Jan 29 '14 at 10:13
$\mathrm{com}(A)$ is the matrix of cofactors associated to $A$. Possibly, it is a French notation, where $\mathrm{com}$ stands for comatrice. – Seirios Jan 29 '14 at 11:56
Hello from 2016! Could you please give a reference to this proof? – Valery Saharov May 17 at 6:35

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.